Durvalumab Monotherapy in Complex Advanced Hepatocellular Carcinoma: A Real‐World Study of Patients Ineligible for Combination Immunotherapy - Chihiro Miwa; Sadahisa Ogasawara; Takuya Yonemoto; Sae Yumita; Tomomi Okubo; Miyuki Nakagawa; Keisuke Koroki; Masanori Inoue; Naoya Kanogawa; Masato Nakamura; Takayuki Kondo; Shingo Nakamoto; et al. (Cancer Medicine)
ABSTRACT Aim Combination immunotherapy is the standard of care for advanced hepatocellular carcinoma (HCC). However, some patients are unsuitable for such treatment. This study investigated the safety and effectiveness of durvalumab monotherapy in a real‐world cohort with advanced HCC who were poor candidates for combination immunotherapy. Methods We retrospectively analyzed data from 35 patients with advanced HCC treated with durvalumab monotherapy across three Japanese institutions between January and December 2023. Patients were selected based on their ineligibility for combination immunotherapy or vascular endothelial growth factor inhibiting tyrosine kinase inhibitors (VEGF‐TKIs). Overall survival (OS), progression‐free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse events (AEs) were assessed. Results The median age was 71 years, with 51.4% classified as Child–Pugh B or C. Notably, 91.4% of patients were ineligible for the IMbrave150 or HIMALAYA trials. Median PFS was 2.7 months (95% CI: 1.84–6.2) and the median OS was not reached. The ORR and DCR were 2.9% and 51.4%, respectively. Grade ≥ 3 treatment‐related AEs (trAEs) occurred in 8.6% of patients, with a discontinuation rate of 11.4% due to AEs. The most common AEs were aspartate aminotransferase (AST) increased (34.3%), hypoalbuminemia (28.6%), and alanine aminotransferase (ALT) increased (25.7%). Immune‐mediated AEs (imAEs) affected 14.3% of the patients. The albumin‐bilirubin (ALBI) scores showed no significant deterioration in patients without progressive disease (PD) over 12 weeks after treatment initiation (p = 0.771). Conclusions Durvalumab monotherapy demonstrated a favorable safety profile and comparable effectiveness to VEGF‐TKIs in patients with advanced HCC unsuitable for combination immunotherapy, especially for those with Child–Pugh B status.